Surfing, self-medicating and safety: buying non-prescription and complementary medicines via the internet. Issue 2 (1st April 2003) - Bessell, T L; Anderson, J N; Silagy, C A; Sansom, L N; Hiller, J E
Abstract : Objective: To examine whether the sale of medicines via the internet supports their safe and appropriate use. Design: e-Pharmacy websites were identified using key words and a metasearch engine and the quality of information published on these websites was surveyed using the DISCERN tool. A case scenario and internet pharmacy practice standards were also used to evaluate the quality of care delivered. Setting and participants: Between July and September 2001 104 websites were surveyed and 27 sent either Sudafed (pseudoephedrine HCl), St John's wort products, or both to a residential address in Melbourne, Australia. Main outcome measures: Quality of health information (DISCERN ratings), information exchanged between e-pharmacy staff and consumers, and product and delivery costs. Results: Of 104 e-pharmacies from at least 13 different countries, 63 websites provided some health information but overall the quality of the information was poor. Only three website operators provided adequate advice to consumers to avoid a potential drug interaction. The costs for a daily dose of pseudoephedrine HCl (240 mg) ranged from A$0.81 to A$3.04, and delivery costs from A$3.28 to A$62.70. Conclusion: Consumers who self-select medicines from websites have insufficient access to information and advice at the point of ordering and on delivery to make informed decisions about their safe and appropriate use.